A Comparison of Small Rodent Assemblages after a 20 Year Interval in the Alps - Ferrari, Giulia; Scaravelli, Dino; Mustoni, Andrea; Armanini, Marco; Zibordi, Filippo; Devineau, Olivier; Cagnacci, Francesca; Grasso, Donato A; Ossi, Federico (Animals, 2023)
Simple Summary The Alps are undergoing important environmental alterations. These can modify the characteristics of the habitats where several wildlife species persist, leading to a reshuffle of local assemblages (i.e., the ensemble of species in a given habitat). We investigated these aspects in alpine small rodents, monitoring their assemblage after a 20 year interval (between 1997 and 2016) in three close-by different habitats (rocky scree, grassland, and heath) at 2100 m a.s.l. elevation. We found that the bank vole, commonly considered a forest-dwelling species, was well-established in these high-alpine habitats already in 1997 and further expanded twenty years later. On the contrary, the snow vole, which is typically resident at these elevations and even above, has restricted its range across decades, being found in 2016 only in the optimal habitat for this species (rocky scree). Given the numerous factors affecting population dynamics in small rodents, it is hard to derive robust inferences from this 'punctual' comparison. The modification of local assemblages might be related to an ongoing modification of the local climate while also being caused by demographic processes typical of small mammal population dynamics. Long-term studies are necessary to better investigate these critical issues. Human-induced environmental alterations in the Alps may importantly affect small mammal species, but evidence in this sense is limited. We live-trapped small rodents in the Central-Eastern Italian Alps in three close-by habitat types (rocky scree, alpine grassland, and heath) at 2100 m a.s.l. during summer-fall, in 1997 and 2016. We compared small rodent assemblages through a Redundancy Detrended Analysis (RDA). In both surveys, we detected two specialist species, i.e., the common vole (Microtus arvalis) and the snow vole (Chionomys nivalis), and, unexpectedly, the forest generalist bank vole (Myodes glareolus). In 1997, grassland was mainly occupied by the common vole, while the bank vole and the snow vole were ...